2020
DOI: 10.3389/fgene.2020.00846
|View full text |Cite
|
Sign up to set email alerts
|

ECRG4 Represses Cell Proliferation and Invasiveness via NFIC/OGN/NF-κB Signaling Pathway in Bladder Cancer

Abstract: Bladder cancer (BCa) is a malignant tumor in the urinary system with high cancer-related mortality worldwide. However, the molecular mechanisms of many genes dysregulated in BCa are still unclear. Herein, we showed that esophageal cancer-related gene-4 (ECRG4), which is downregulated in BCa tissues and cell lines, has a positive correlation with osteoglycin (OGN). Further functional experimental studies suggested that both ECRG4 and OGN inhibit cell proliferation, migration, and invasion in BCa cells. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Furthermore, we clarified that MCPIP1 promoted the production of CTF5 by regulating exons 9 and 10 skipping in NFIC . Several studies have demonstrated that NFIC acted as an antioncogene in multiple cancers, including esophageal squamous cell cancer 52 , bladder cancer 53 , breast cancer 54 . Nevertheless, the exact roles of CTF5 in TNBC still need to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we clarified that MCPIP1 promoted the production of CTF5 by regulating exons 9 and 10 skipping in NFIC . Several studies have demonstrated that NFIC acted as an antioncogene in multiple cancers, including esophageal squamous cell cancer 52 , bladder cancer 53 , breast cancer 54 . Nevertheless, the exact roles of CTF5 in TNBC still need to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that NFIC belongs the NFI family of site-specific transcription factors, which can modulate cancer-related genes transcription in various cancers 42 , 53 55 . Previously, NFIC was demonstrated to directly repress cyclin D1 transcription in breast cancer 42 .…”
Section: Discussionmentioning
confidence: 99%
“…An existing research determined the inhibitory role of NFIC in the invasion, migration, or metastasis via suppression of EMT in esophageal squamous cell cancer [ 19 ]. Similarly, NFIC has been implicated in the treatment of bladder cancer and glioblastomas [ 36 , 37 ]. Altogether, METTL3 elevated the miR-20a-5p expression to inhibit NFIC transcription, thereby facilitating EMT, metastasis, and invasion in ESCA.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse range of the target substrates of NFIC confers its multiple biological functions. For instance, NFIC can promote osteoglycin expression by binding to its promoter region to repress bladder cancer by limiting cell proliferation and invasiveness [ 50 ]. Nevertheless, the transcriptional role of NFIC on miRNA is still uncertain.…”
Section: Discussionmentioning
confidence: 99%